(untitled) (Minerva, 2019)
The aim of this article is to emphasize the relationship between Erasmus’ Adagia and the Lectiones Antiquae by Caelius Rhodiginus. By comparing both works we have found several cases of plagiarism in both directions. In this article we present some examples of passages in which that influence can be seen.